The emergence of early Yiddish literature : cultural translation in Ashkenaz - Frakes, Jerold C. (German Jewish cultures., 2017)
While much early Yiddish literature belonged to pious genres, quasi-secular genres epic, drama, and lyric also developed. Jerold C. Frakes contends that the historical context of the emergence of Yiddish literature is an essential factor in any understanding of its cultural relevance in a time and place where Jewish life was defined by expulsions, massacres, and discriminatory legislation that profoundly altered European Judaism and shook the very foundations of traditional Jewish society.